CFO narcissism and the power of persuasion over analysts: a mixed-methods approach - Ham, Charles; Piorkowski, Mark; Seybert, Nick; Wang, Sean (Review of Accounting Studies, 2025)
We study the role of CFO narcissism in the intent and ability to positively influence sell-side analysts’ perceptions of the firm. Consistent with narcissists casting favorable impressions on others, we find CFO narcissism is associated with overly optimistic analyst valuations. We then study public persuasion attempts by analyzing conference call transcripts and private persuasion attempts through a laboratory study. In the conference call setting, we show that narcissistic CFOs use more persuasive language and are more inclined to call on bearish analysts, both of which we link to price target revisions following the call. In the lab study, we simulate a one-on-one conversation and find that narcissists are especially more likely to use coercive methods to induce higher valuations from analysts. Collectively, we show that narcissistic CFOs use persuasion to favorably influence analysts’ perceptions of firm value.